2012
DOI: 10.1111/j.1365-2044.2011.07051.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posture and anaesthetic technique on the surgical pleth index

Abstract: SummaryThe surgical pleth index has been shown to correlate with surrogate variables of nociception during general anaesthesia, and it has been suggested to be of use as a depth of anaesthesia monitor. However, little is known about confounding factors. As the main determining variables are based on both central and peripheral autonomic regulatory mechanisms, we hypothesised that changing a patient's posture may produce a marked effect. We studied the effects of posture change in 45 patients who were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Although pre‐clinical and clinical (intra‐operative and postoperative) research indicated its ability to discriminate strong noxious stimuli from no stimulation , the method could not consistently differentiate stimulus intensities . The surgical plethysmographic index is not specific to nociception, and is influenced by both peripheral and central sympathetic tone , sex , intravascular volume status , heart rate , drugs , location of the probe , posture , levels of consciousness and in awake patients, pain anticipation and emotional stress. Although the non‐invasive nature of the clinical application is appealing, this is offset by large inter‐patient variability.…”
Section: Resultsmentioning
confidence: 98%
“…Although pre‐clinical and clinical (intra‐operative and postoperative) research indicated its ability to discriminate strong noxious stimuli from no stimulation , the method could not consistently differentiate stimulus intensities . The surgical plethysmographic index is not specific to nociception, and is influenced by both peripheral and central sympathetic tone , sex , intravascular volume status , heart rate , drugs , location of the probe , posture , levels of consciousness and in awake patients, pain anticipation and emotional stress. Although the non‐invasive nature of the clinical application is appealing, this is offset by large inter‐patient variability.…”
Section: Resultsmentioning
confidence: 98%
“…We also avoided patients in a steep Trendelenburg or anti-Trendelenburg position because this has been found to alter SPI. 13 The SPI values obtained in everyday clinical practice may therefore be different. However, the limitation of SPI recordings to the last 10 min of surgery may make the cut-off suggested by us a bit more useful.…”
Section: Discussionmentioning
confidence: 99%
“…11,[24][25][26] These effects are the principal determinants of PPGA changes because of sympathetic stimulation. [31][32][33][34] All these factors alter the ANS without affecting the nociception. The blood volume pulsations (ΔV) are related to both the systemic intravascular pulse pressure (ΔP) and the distensibility of the vascular wall (D) according to the relationship: 27 The distensibility is influenced by intravascular volume status and sympathetic activity directed to the vessels, whereas vagal fibers are absent in the peripheral vascular bed.…”
Section: Autonomic Estimation By Photoplethysmographymentioning
confidence: 99%